Thermoelastic free vibration response of graphene reinforced laminated composite shells. (1st January 2019) - Rout, Mrutyunjay; Hota, Sasank Shekhar; Karmakar, Amit
Highlights: Graphene reinforced singly/doubly curved shells are analyzed in thermal environment. Finite element formulation based on HSDT is presented. Four types of reinforcement of graphene sheet are considered in each shell. Parametric studies are presented. Abstract: This article deals with the free vibration analyses of graphene reinforced singly and doubly curved laminated composite shell panels in thermal environment using finite element method. The curved shell panels are mathematically modeled using higher order shear deformation theory (HSDT) while the distortion of the geometry due to thermal loading is manifested through geometric stiffness considering Green Lagrange type of nonlinearity. Four different types of graphene reinforcement configurations are considered in different types of shells (cylindrical, elliptic paraboloid, hyperbolic paraboloid, conoidal and hypar). The extended Halpin–Tsai approach is used to obtain the temperature dependent material properties of the laminated composite shells. Eight noded isoparametric shell elements consisting of seven degrees of freedom per node are considered to discretize the geometry. The accuracy and convergence of the formulation are verified by solving various examples available in the literature. Finally, parametric study is presented to investigate the influence of various parameters on the free vibration response of the graphene reinforced laminated composite shells.